(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to assess the prevalence of poor sleep quality, anxiety, depression, and stress among university students. Methods: A cross-sectional study was conducted on 124 students from various majors at a private university in Hanoi. Data was collected via an anonymous online survey using the Pittsburgh Sleep Quality Index (PSQI) and Depression-Anxiety-Stress Scale (DASS-21). Descriptive statistics and chi-square, Fisher’s Exact, and Monte Carlo tests were used. Results: Poor sleep quality was reported by 81.5% of students, higher than national and global averages. Symptoms of depression, anxiety, and stress were found in 56.5%, 68.5%, and 36.3% of students, respectively. Conclusion: The high prevalence of poor sleep and mental health symptoms highlight the need for comprehensive mental health support and interventions from the university.